Antonia Baehr’s My Dog is my Piano and Abecedarium Bestiarium: Theatre of the Bestiary, Bestiaries of Theatre - Esther Köhring (Sillages Critiques)
This paper investigates the historical and systematical relationship between theatre and the bestiary, presenting some methodological considerations for thinking about and with animals on stages. The argument combines material from theory of the bestiary (bestiaries as figuration of theory), as well as from the cultural history of the bestiary (bestiaries as cultural form) with an analysis of the work of contemporary German choreographer and performer Antonia Baehr. Her latest solo performances are deeply informed by the current debates about the human-animal relationship and explore theatre’s role in thinking about and dealing with animals.